2008
DOI: 10.1038/eye.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Heavy tamponade 2 Densiron 68® in routine clinical practice: anatomical and functional outcomes of a consecutive case series

Abstract: Purpose To evaluate the safety and efficacy of Densiron 68 s in the clinical management of complex vitreoretinal cases with inferior retinal pathology. Methods We present a prospective interventional non-comparative case series of 122 eyes of 121 consecutive patients. The primary end point was anatomical reattachment of the retina, defined as retinal reattachment in the absence of any tamponade agent. The secondary end point was to record the visual function and surgical complications. Inclusion criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
7
29
0
4
Order By: Relevance
“…A higher rate of rise in IOP could be noted in 8-30% patients with Densiron 68 tamponade. 11,18,21,22 This was similar to the results of our study, in which we reported that the incidence of elevated IOP after Densiron 68 tamponade was 18.5%. At 1 week and 1 month after heavy oil operation, five patients presented with an IOP higher than 30 mmHg, and at study end, 3 months after oil removal, no patient had raised IOP higher than 20 mmHg.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A higher rate of rise in IOP could be noted in 8-30% patients with Densiron 68 tamponade. 11,18,21,22 This was similar to the results of our study, in which we reported that the incidence of elevated IOP after Densiron 68 tamponade was 18.5%. At 1 week and 1 month after heavy oil operation, five patients presented with an IOP higher than 30 mmHg, and at study end, 3 months after oil removal, no patient had raised IOP higher than 20 mmHg.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were obtained in large studies involving 99 and 121 cases. 18,21 With Densiron 68, dispersion occurred in 16 (6/42) and 15% (7/48), 11,19 remarkable emulsification encountered in 16.7 (2/12) and 10% (1/10) after 1-year follow-up. 12,22 Only one of the cases described by Sandner and Engelmann 19 had increased IOP; nevertheless, the authors recommend anterior chamber washout in all patients at the time of Densiron 68 removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in eyes with scleral buckling, endotamponade with Oxane HD was found to have low retinal reattachment success rates (26%); the authors suggest that this may be due to poor affinity to the retinal surface, or insufficient specific density to provide adequate tamponade to areas adjacent to the indent [7]. The retinal reattachment rate with Densiron 68 endotamponade was 33–91% after the initial procedure, and 75–94% with further surgery [11,12,13,14,15,16,17]. It had been observed that Densiron 68 enabled better anatomic reattachment for complicated RD when compared to conventional 5,000-cs silicone oil, but adverse effects were similar [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports and studies on the use of Densiron 68 in complicated retinal detachment have been published in the last few years [66,67,68,69,70,71,72,73,74,75,76,77]. Primary anatomical outcome rates have varied between 33 and 91%, with final anatomical success rates varying between 75 and 94%.…”
Section: Endotamponades Heavier Than Watermentioning
confidence: 99%